A Magyar Posta szerepe a logisztikai piacon - Juhász Alexandra (2016)
The study describes the role of a state-owned company in the logistics market, describing the essence, concept and role of logistics. It follows the history of the Hungarian Post Of-fice from the beginning to the present day. The main focus of the analysis is on the goals that have been achieved, and the large amount of work that has been invested in the company.We get an insight to what some competitors have achieved so far compared to the Hungarian Post. While comparing the competitors’ achieved data to the post office, it explains the leadership in the CEP market since 2008. The overall market situation is analized for 2014 and 2015. Also, e-commerce is looked at and we understand why it is known as the main driver for package traffic In today's busy world it is the really important for everyone that anything can be arranged when people want itt o. People do not like to wait, everyone is in a hurry either to his family or workplace, and just can not stand in queues. The study shows how technologies developed and describes in detail how it makes life easier. It gives an overview of a consignment varieties, in order to visualize many ways it can meet the customers’ needs. Whether it's quick, expensive, time consuming or cheap. We can find out where the processes are happening, how much time and labor is required so that work is done in one night to send hundreds of express parcels. It also examines, who and what kind of machines are doing the selection process. During the processing not only packages, but any other post office processes are looked at. Finally, Sopron's post office, which is located close to the border, is introduced using charts and tables which are easy to understand, especially what Christmas means for the post office. Innovations and automatic package machines are introduced, as well as the well-established MOL points.